2012
DOI: 10.1007/s10512-012-9524-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 137Cs decontamination of concrete by the reagent method

Abstract: The particulars of radioactive contamination of concrete wastes by 137 Cs were studied. x-Ray phase analysis and chemical analysis show that clayey materials, including Al 2 O 3 , Fe 2 O 3 , K 2 O, and MgO, on which 137 Cs sorption is possible, were present in the concrete wastes. The content and form in which 137 Cs was found in radioactive concrete wastes from nuclear power facilities as well as in model samples were determined. When the wastes were treated with nitric acid the binder dissolved and a polydis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In respect of cesium in concrete, Nikolayev et al suggested that clayey minerals and cement binder is the main source of cesium in concrete. 64 In addition, they suggested that 30-50% of the 137 Cs in concrete is in a fixed form, and only 5% of the total amount of 137 Cs is highly fixed in concrete. Cesium is one of the elements that contaminates concrete by direct penetration, thus most of the cesium isotopes might bond to the concrete microstructure through adsorption.…”
Section: Bonding Forms Of Nuclides In Radioactive Concrete Waste-thementioning
confidence: 99%
See 4 more Smart Citations
“…In respect of cesium in concrete, Nikolayev et al suggested that clayey minerals and cement binder is the main source of cesium in concrete. 64 In addition, they suggested that 30-50% of the 137 Cs in concrete is in a fixed form, and only 5% of the total amount of 137 Cs is highly fixed in concrete. Cesium is one of the elements that contaminates concrete by direct penetration, thus most of the cesium isotopes might bond to the concrete microstructure through adsorption.…”
Section: Bonding Forms Of Nuclides In Radioactive Concrete Waste-thementioning
confidence: 99%
“…85 However, the trend observed by Faiz et al and Nikolayev et al differed from that of Rahman et al for the mobility of cesium. 31,77,85 Fig . 21 shows the cumulative leaching rate of cesium in Portland cement mortar for different time intervals (0-7 days, 7-16 days, 16-23 days, 23-34 days).…”
Section: Dec =mentioning
confidence: 99%
See 3 more Smart Citations